Förekomst av önskvärda beteenden och stereotypier i relation till utevistelse hos giraffer (Giraffa camelopardalis) på Borås djurpark - Zedén, Sarah (2020)
In the wild, giraffes spend most of their day foraging and thus are most commonly found on the savannah where there is plenty of greenery. They continuously move to meet their daily nutritional need and can move over up to 437 km2 . Their diet is rich in fibre and consists mostly of leaves, twigs and bark. Typically, the giraffe spends mornings and evenings foraging and ruminating during the hottest part of the day. The social structure in the giraffe herd is a fission-fusion system, where individuals come and go on a daily basis. It is difficult to reconstruct a natural life for giraffes in captivity, as limitations in form of space is a major problem. From practical and economical aspects, it is difficult to recreate their natural diet as well. Instead, captive giraffes are generally fed with feed appropriate for our domesticated ruminants. However, the majority of zoos strive toward letting captive animals perform as many natural behaviors as possible. The possibility to perform natural behavior tends to reduce the risk of animals developing stereotypic behavior. Furthermore, studies have shown that the size of the enclosure also has an impact on the time captive giraffes spend ruminating and exhibit locomotive behavior. This study was conducted to examine how access to an outdoor area affected the occurrence of natural and stereotypic behavior in giraffes at Borås zoo, Sweden. The giraffes were observed during two treatments, one with access to the outdoor area and one without, in order to collect data which later were compared. The results suggested that occurrence of natural and stereotypic behavior is related to the possibility to access an outdoor area. When the giraffes had access to the outdoor enclosure, the prevalence of stereotypies decreased, whilst the prevalence of natural behavior increased. These findings suggest that outdoor access has an impact on the behavior of the captive giraffe, but more studies need to be conducted to investigate whether it is possible to apply these findings to giraffes in other zoos.